Geçmişten bugüne Ali Suavi, ¨Talim ü Terbiye¨ , İslam Dünyası 2/2 (1331), s. 24-25. - Deva Güneş (Sakarya University Journal of Education)
Geçmişten bugüne Ali Suavi, ¨Talim ü Terbiye¨ , İslam Dünyası 2/2 (1331), s. 24-25.